Effect of Dynamic Soil-Structure Interaction on Raft of Piled Raft Foundation of Chimneys. (20th January 2014) - Jayalekshmi, B. R.; Jisha, S. V.; Shivashankar, R.; Soorya Narayana, S.
Abstract : This paper presents numerical analysis of soil-structure-interaction (SSI) of tall reinforced concrete chimneys with piled raft foundation subjected to El Centro ground motion (1940) using finite element method. Seismic analysis in time domain was performed on the basis of direct method of SSI on the three-dimensional SSI system. The chimney, foundation, and soil were assumed to be linearly elastic in the analysis. The stress resultants and settlement of raft of piled raft foundation were evaluated under different soil properties and different geometrical features of raft and chimney. Soil properties were selected based on the shear wave velocity corresponding to sand in the loose to dense range. Chimneys with different elevations of 100 m, 200 m, and 400 m were taken with a ratio of height to base diameter of chimney of 17. Raft of different thickness was considered to evaluate the effect of stiffness of foundation. Results were analysed to assess the significance of characteristic of the ground motion. It is found that the response in the raft depends on the different parameters of chimney, foundation, and soil. It is also found that the higher modes of SSI system are significant in determining the response in the raft.